Advantages of implementing mediamorphosis in supporting Using-ethnic programs at Radio Sritanjung FM Banyuwangi - Zainal Abidin Achmad; Juwito Juwito; Yuli Candrasari; Asia Ashfaq (Masyarakat, Kebudayaan dan Politik, 2021)
Many private radio businesses have experienced a decline in advertising revenue during the COVID-19 pandemic; however, this did not happen to Radio Sritanjung FM Banyuwangi, which implemented mediamorphosis to support its broadcasts. This study aims to map the application of mediamorphosis in supporting the broadcast of cultural programs on Radio Sritanjung FM, Banyuwangi, East Java, Indonesia. This study used a qualitative virtual ethnographic method, which requires researchers to enter two research areas: the natural world and the virtual world. Researchers interacted freely with eight informants, such as Using-ethnic figures, Muslim leaders, radio station management, local advertisers, and loyal listeners through in-depth interviews and Focus Group Discussions (FGD) to understand the ongoing mediamorphosis process in a virtual network. The research analysis using network society theory shows that the mediamorphosis process of Radio Sritanjung FM began in 2011 with Facebook, Instagram, and Twitter. The latest technology application is audio streaming to support, promote, and disseminate the Using’s ethnic culture to foreign countries. The application of mediamorphosis during the COVID-19 pandemic presents a harmonization between cultural programs and Islamic religious values, strengthening the local identity of the Using-ethnicity, and increases financial benefits.